(untitled) (Stamford Journal of Pharmaceutical Sciences, 2009)
Analgesic and central nervous system depressant activity of the methanol extract of Achyranthes aspera Linn. was assessed by using acetic acid induced writhing test, thiopental sodium induced sleeping time determination, hole cross test and open field test in albino mice. The extract (250 and 500mg/kg) showed a dose dependent inhibition of writhing response generation by acetic acid compared to reference drug diclofenac sodium (50mg/kg). Methanol (70%) extract of Achyranthes aspera (500 mg/kg) also produced rapid onset and maximized the duration of sleeping time when administered with thiopental sodium. The extract also decreased the motor activity and exploratory behavior of mice in hole cross and open field test. The overall experimental results suggest the analgesic and central nervous system depressant activity of the methanolic extract of Achyranthes aspera and justify its use in folkloric remedies. Key Words: Achyranthes aspera, Analgesic activity, Central nervous system depressant activity. doi:10.3329/sjps.v1i1.1807 S. J. Pharm. Sci. 1(1&2): 44-50